Seagrass-associated fish species’ richness: evidence to support conservation along the south coast of Lombok Island, Indonesia - Abdul Syukur; Agil Al Idrus Idrus; Lalu Zulkifli (Society for Indonesian Biodiversity, 2021)
Abstract. Syukur A, Al-Idrus A, Zulkifli L. 2021. Seagrass-associated fish species’ richness: evidence to support conservation along the South Coast of Lombok Island, Indonesia. Biodiversitas 22: 988-998. The concept of seagrass conservation at a global scale tends to be less appropriate with regard to the environmental conditions at the regional and local scales, and thus, there is a need for scientific studies at the regional and local scales to support conservation measures. This research aimed to describe the importance of seagrass conservation based on the species richness of seagrass-associated fish. Data were collected from seven seagrass locations using surveys and observation. Data on the fish species present were collected with the gear used by small-scale fishermen to catch fish in the seagrass area and the surrounding waters. Data analysis was descriptive; the statistical analyses performed included calculation of the Shannon-Wiener index of diversity (H '), the Simpson evenness index (E), and the Morisita species richness index (D) as well as cluster analysis. All statistical analyses were performed in IBM SPSS Statistics 25. We found 104 fish species belonging to 38 families. Leiognathidae, Apogonidae, Clupeidae, Carangidae, Channidae, Sillaginidae, and Mullidae are families with high abundance, and 16 fish species have an abundance of individuals above the average value (192 individuals) of the total number of individuals (20,352). Meanwhile, 94.37% of the fish families are the target catch of small-scale fishermen (commercial fish). The diversity of fish species associated with seagrass in the study location is evidence of the survival of seagrass provision services at the local scale for fish. Therefore, scientific evidence of the species richness of fish, species yang domina, and its importance for small-scale fisheries at each seagrass bed in the study location can be used as a source of information for increasing and improving seagrass conservation efforts at the local scale.